Late Quaternary sedimentary evolution of the outer shelf of the East China Sea. (10th November 2018) - Xu, Taoyu; Shi, Xuefa; Liu, Shengfa; Qiao, Shuqing; Yao, Zhengquan; Fang, Xisheng; Wu, Yonghua; Shan, Xin; Liu, Jianxing; Yang, Gang; Liu, Chenguang; Li, Xiaoyan; et al.
Abstract: This study investigated the late Quaternary sedimentary evolution of the outer shelf of the East China Sea (ECS) using borehole core data (DH02). Three unconformity-bounded sedimentary facies, namely, prodelta facies of marine isotopic stage (MIS) 3, intertidal to subtidal flat facies of the deglacial period, and offshore tidal sand ridge facies of the Holocene, were identified from the base upward according to combined evidence of lithology, microfossil assemblages, and geochronology. Through comparative analysis with other neighboring borehole cores, these three facies, along with the MIS 3 nearshore facies and the last glacial maximum (LGM) river facies, were found to constitute the late Quaternary sediment strata. Sedimentary processes of these five facies were interpreted based on a synthetic consideration of sea-level change, climate variation, paleotopographic setting, and paleoriver-sea interactions. In particular, the development of the delta was attributable to integration of the slow sea-level decline during the later stage of the MIS 3 and abundant sediment supply resulting from the warm-wet climate. The gentle shelf topography suggests the presence of shallow and wide rivers in the delta, and the lateral shift of river channels might have induced the local formation of nearshore facies at the abandoned river mouth. The LGM river facies, which was rarely observed (presumably due to marine erosion with deglacial transgression), was inferred to have been deposited during the latter half of the LGM in response to the rise in river base level. Occurrences of tidal flat facies imply the formation of a tide-dominated estuary with the deglacial transgression. Furthermore, tidal flat sediments were reworked by enhanced tidal currents in the estuary front environment, forming mud ridges during subsequent deglacial transgression. Formation of tidal sand ridges in offshore environments of the Holocene was attributable to the uneven base caused by the underlying estuarine erosion mud ridges, and this promoted the occurrence of tidal depositional processes. The sedimentary evolution in association with sea-level change was constructed using the above-mentioned results. Overall, this study systematically elucidates the late Quaternary sedimentary processes and evolution of the outer ECS shelf, and provides an insight into the sedimentary development of analogous shelves around the world.